Promotors in Regional Innovation Systems – Three Examples from Northwest Germany - Klein, Oliver; Gronemeyer, Christine Marie; Maschinski, Sascha; Born, Karl Martin (Raumforschung und Raumordnung | Spatial Research and Planning, 2016)
The organization of regional innovation systems is mostly complex and results not only from specific conditions on-site, but also from networking activities of individual actors. In this respect, economic development agencies play a key role, particularly as their responsibilities normally include the initiation and support of innovation processes. In order to ensure this, economic development agencies in practice often enter into joint collaboration with special innovation consultants. These actors are strongly interlinked with potential innovation partners enabling them to support innovation processes, especially in small and medium-sized enterprises. Due to this network capability, economists have established the role model of the relationship promotor which is in the focus of this paper. Taking the example of three regions in Northwest Germany, we analyze the function of economic development agencies and innovation consultants as relationship promotors and their specific strategies affecting the configuration of different innovation systems. It will be shown that the three regions – district of Oldenburg, Oldenburger Münsterland, Elbe-Weser region – adopt different strategies varying in terms of territorial dimension, range of actors and degree of networking. Basically, the configuration of regional innovation systems to a large extent depends on various sources of power of the operating promotors. Apart from three typical sources of power which can be found in the literature – social competence, networking knowledge, relationship patterns – the empirical analysis also reveals the reputation of relationship promotors as additional factor of being able to exert influence.
Keywords: Innovation systems; Relationship promotors; Knowledge transfer; Economic development; Northwest Germany